RUM(I)S AS THE REFERENCE TO THE TURKS AND PERCEPTIONS IN THE MALAY WORLD - Ã–zay, Mehmet (Journal of Al-Tamaddun, 2020)
Rumis, who are identified as the seafarers and warriors in the Ottoman State, had an impact in the regions as a diasporic group exercising their professions from the West Asia through India and till Southeast Asia. It is comprehended that this concept, referring to both a geographical and cultural environment, was diffused among distinct state’s formations throughout the centuries in the Asia Minor. Pertaining to Islamization of Turks and their gaining territorial sovereignty in that geography, a certain group of people classified under this title became subject of mobilization by some explicit reasons. In particular, the awareness of the relevant geographies, expansion of trade routes and the requirement of the skilled warriors by the principalities in North-Western Indian and Malay Archipelago are the reasons for the small or larger groups of Rumis to have travelled by their own capacities under certain conditions to some extent, beyond their function in the expansion process of the Ottoman State. This research is based on some primary sources including archival documents and secondary works from distinct geographies which are taken into consideration by comparative and interpretation approaches. The present writer briefly discusses the existence of Rumis, how this group represented themselves in the adjacent regions to the Indian Ocean and in which way the the concept of Rum/is was perceived, in particular, in the Malay genealogies and people in general in the course of time.